Persuasive writing : grades 3-5 - Rozmiarek Rebecca; Migliaccio, Eric. (Westminster, CA : Teacher Created Materials, 2000)
Activities in this book have been divided into three categories: letters, editorials, and reviews. Incorporated throughout the book are standards for assessment.
Keywords: Persuasion (Rhetoric) -- Problems, exercises, etc; English language -- Composition and exercises -- Study and teaching (Elementary); Language arts (Elementary)